1835 Ark. Terr. Laws 521 - (:unkn) unknown (My University, 1835)
No slave or mulatto whatsoever, shall keep or carry a gun, powder, shot, club or other weapon whatsoever, offensive or defensive; but all and every gun weapon and ammunition found in the possession or custody of any negro or mulatto, may be seized by any person and upon due proof made before any justice of the peace of the district [county] where such seizure shall be, shall by his order be forfeited to the seizor, for his own use, and moreover, every such offender shall have and receive by order of such justice any number of lashes not exceeding thirty nine on his or her bare back well laid on for every such offense.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES